2014
DOI: 10.1177/1066896914541000
|View full text |Cite
|
Sign up to set email alerts
|

Jaw Cysts Diagnosed in an Italian Population Over a 20-Year Period

Abstract: Our study confirms that the distribution pattern of JCs in Italy is relatively similar to other studies worldwide and emphasizes the importance of recognizing the different histological types of JCs for their potential local aggressive behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 31 publications
15
18
0
1
Order By: Relevance
“…The anterior maxilla was the most affected region by both PG and PC, similarly to the data retrieved from the literature ( 2 - 4 , 8 - 10 ). Meningaud et al ( 13 ) and Del Corso et al ( 24 ) reported that PC predominantly affected the mandible, in contrast with most published studies. Our results showed that the distribution of the anatomical location comparing PG and PC was significantly different.…”
Section: Discussionmentioning
confidence: 91%
“…The anterior maxilla was the most affected region by both PG and PC, similarly to the data retrieved from the literature ( 2 - 4 , 8 - 10 ). Meningaud et al ( 13 ) and Del Corso et al ( 24 ) reported that PC predominantly affected the mandible, in contrast with most published studies. Our results showed that the distribution of the anatomical location comparing PG and PC was significantly different.…”
Section: Discussionmentioning
confidence: 91%
“…The dentigerous cyst (DC) is the second most common odontogenic cyst of the jaw, after the radicular cyst, and accounts for 20-30% of all jaw cysts. The cysts are thought to arise from the reduced enamel epithelium of unerupted teeth and are most common in the first to third decades and arising from the third molar, particularly in the mandible [4][5][6] .…”
Section: Dentigerous Cystsmentioning
confidence: 99%
“…O COG é uma lesão rara, representando apenas 0,2% a 0,8% de todos os cistos odontogênicos, 5,13,14 que compartilha algumas das suas características microscópicas com outras lesões císticas e neoplásicas. 8,15 A etiologia do COG, que tem sua histogênese relacionada aos remanescentes da lâmina dentária, permanece desconhecida.…”
Section: Discussionunclassified